Вимірювання параметрів несиметричних швидкозмінних трифазних навантажень - Бурбело, М.Й.; Мельничук, С.М.; Никитенко, М.В. (Технічна електродинаміка, 2011)
Measurement of parameters of asymmetrical quick-change three-phase loadings In the article the method of measurement as well as the measuring channel of parameters of asymmetrical three-phase loadings founded on instantaneous power integration on sliding time lag with the duration of supply voltage half-period has been offered. The measuring channel has sufficient resistance and is characterized by absence of truncation errors of measurements if there is asymmetry between three-phase voltage and higher harmonic of loading current.